Tandem polymer solar cells: simulation and optimization through a multiscale scheme - Wei, Fanan; Yao, Ligang; Lan, Fei; Li, Guangyong; Liu, Lianqing (Beilstein Journal of Nanotechnology, 2017)
In this paper, polymer solar cells with a tandem structure were investigated and optimized using a multiscale simulation scheme. In the proposed multiscale simulation, multiple aspects – optical calculation, mesoscale simulation, device scale simulation and optimal power conversion efficiency searching modules – were studied together to give an optimal result. Through the simulation work, dependencies of device performance on the tandem structures were clarified by tuning the thickness, donor/acceptor weight ratio as well as the donor–acceptor distribution in both active layers of the two sub-cells. Finally, employing searching algorithms, we optimized the power conversion efficiency of the tandem polymer solar cells and located the optimal device structure parameters. With the proposed multiscale simulation strategy, poly(3-hexylthiophene)/phenyl-C61-butyric acid methyl ester and (poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)])/phenyl-C61-butyric acid methyl ester based tandem solar cells were simulated and optimized as an example. Two configurations with different sub-cell sequences in the tandem photovoltaic device were tested and compared. The comparison of the simulation results between the two configurations demonstrated that the balance between the two sub-cells is of critical importance for tandem organic photovoltaics to achieve high performance. Consistency between the optimization results and the reported experimental results proved the effectiveness of the proposed simulation scheme.
Keywords: genetic algorithm; Monte Carlo simulation; simplex searching; tandem polymer solar cells

(untitled) - Li, G.; Shrotriya, V.; Huang, J. S.; Yao, Y.; Moriarty, T.; Emery, K.; Yang, Y. (Nat. Mater., 2005)

(untitled) - Scharber, M. C.; Mühlbacher, D.; Koppe, M.; Denk, P.; Waldauf, C.; Heeger, A. J.; Brabec, C. L. (Adv. Mater., 2006)

(untitled) - He, Z. C.; Zhong, C. M.; Su, S. J.; Xu, M.; Wu, H. B.; Cao, Y. (Nat. Photonics, 2012)

(untitled) - Park, H. J.; Kang, M.-G.; Ahn, S. H.; Guo, L. J. (Adv. Mater., 2010)

Reported timeline of solar cell energy conversion efficiencies - National Renewable Energy Laboratory

(untitled) - You, J. B.; Dou, L. T.; Yoshimura, K.; Kato, T.; Ohya, K.; Moriarty, T.; Emery, K.; Chen, C.-C.; Gao, J.; Li, G.; Yang, Y. (Nat. Commun., 2013)

(untitled) - Kouijzer, S.; Esiner, S.; Frijters, C. H.; Turbiez, M.; Wienk, M. M.; Janssen, R. A. J. (Adv. Energy Mater., 2012)

(untitled) - Kim, J. Y.; Lee, K.; Coates, N. E.; Moses, D.; Nguyen, T.-Q.; Dante, M.; Heeger, A. J. (Science, 2007)

(untitled) - McMeekin, D. P.; Sadoughi, G.; Rehman, W.; Eperon, G. E.; Saliba, M.; Horantner, M. T.; Haghighirad, A.; Sakai, N.; Korte, L.; Rech, B.; Johnston, M. B.; Herz, L. M.; et al. (Science, 2016)

(untitled) - Lu, S.; Guan, X.; Li, X.; Sha, W. E. I.; Xie, F.; Liu, H.; Wang, J.; Huang, F.; Choy, W. C. H. (Adv. Energy Mater., 2015)

(untitled) - Li, K.; Li, Z.; Feng, K.; Xu, X.; Wang, L.; Peng, Q. (J. Am. Chem. Soc., 2013)

(untitled) - Dou, L.; You, J.; Yang, J.; Chen, C.-C.; He, Y.; Murase, S.; Moriarty, T.; Emery, K.; Li, G.; Yang, Y. (Nat. Photonics, 2012)

(untitled) - Li, W.; Furlan, A.; Hendriks, K. H.; Wienk, M. M.; Janssen, R. A. J. (J. Am. Chem. Soc., 2013)

(untitled) - Zhou, Y.; Fuentes-Hernandez, C.; Shim, J. W.; Khan, T. M.; Kippelen, B. (Energy Environ. Sci., 2012)

(untitled) - Gevaerts, V. S.; Furlan, A.; Wienk, M. M.; Turbiez, M.; Janssen, R. A. J. (Adv. Mater., 2012)

(untitled) - Namkoong, G.; Boland, P.; Lee, K.; Dean, J. (J. Appl. Phys., 2010)

(untitled) - Boland, P.; Lee, K.; Dean, J.; Namkoong, G. (Sol. Energy Mater. Sol. Cells, 2010)

(untitled) - Dennler, G.; Forberich, K.; Ameri, T.; Waldauf, C.; Denk, P.; Brabec, C. J.; Hingerl, K.; Heeger, A. J. (J. Appl. Phys., 2007)

(untitled) - Persson, N.-K.; Inganäs, O. (Sol. Energy Mater. Sol. Cells, 2006)

(untitled) - Zuo, L. J.; Chang, C.-Y.; Chueh, C.-C.; Zhang, S.; Li, H.; Jen, A. K.-Y.; Chen, H. (Energy Environ. Sci., 2015)

(untitled) - Bottenfield, C. G.; Wei, F.; Park, H. J.; Guo, L. J.; Li, G. (Energy Technol., 2015)

(untitled) - Burkhard, G. F.; Hoke, E. T.; McGehee, M. D. (Adv. Mater., 2010)

(untitled) - Gu, Y.; Wang, C.; Russell, T. P. (Adv. Energy Mater., 2012)

(untitled) - Morana, M.; Wegscheider, M.; Bonanni, A.; Kopidakis, N.; Shaheen, S.; Scharber, M.; Zhu, Z.; Waller, D.; Gaudiana, R.; Brabec, C. (Adv. Funct. Mater., 2008)

Performance optimization of organic solar cells by simulation and characterization - Liu, L. (University of Pittsburgh, 2011)

(untitled) - Hoppe, H.; Arnold, N.; Sariciftci, N. S.; Meissner, D. (Sol. Energy Mater. Sol. Cells, 2003)

(untitled) - Wei, F.; Liu, L.; Liu, L.; Li, G. (IEEE J. Photovoltaics, 2013)

(untitled) - Nakamura, J.-i.; Murata, K.; Takahashi, K. (Appl. Phys. Lett., 2005)

(untitled) - Pandey, S. S.; Takashima, W.; Nagamatsu, S.; Endo, T.; Rikukawa, M.; Kaneto, K. (Jpn. J. Appl. Phys., Part 2, 2000)

(untitled) - Nelder, J. A.; Mead, R. (Comput. J., 1965)

(untitled) - Barricelli, N. A. (Methodos, 1957)